The learning effects of flipped classroom on nursing student’s vital signs knowledge, skill, and satisfaction: Post-test only control group study - Kaliyaperumal, Raji; Jeyapaul, Shylaja; Ahamed Mohammed Mohammed, Khalda; Hussain Madani, Amna; Hassan Merghani Mohammed, Duria (Edelweiss Applied Science and Technology, 2024)
The Traditional lectures optimize the passive learning, where students attend passively, however, lacking a deep understanding of the lecture material. Consequently, an innovative teaching approach is necessary to develop student engagement, active learning, and critical thinking skills. The aim of the study is to evaluate the effect of flipped classroom on knowledge, skill, and satisfaction about vital signs nursing procedure. A post-test only control group design study was carried out in College of Nursing, Muhayil. King Khalid University, Kingdom of Saudi Arabia, during May 2024. The study population consisted of 63 second year Baccalaureate nursing students. A Simple random sampling technique was adopted to recruit samples in an experimental and control group. An Experimental group received flipped class model teaching and the control group received traditional method of teaching about vital signs nursing procedure. Knowledge was assessed using self-reported questionnaire, and skill by checklist also Satisfaction about the teaching method was assessed using 5-point likert scale. It is shown that there is a significant difference in the scores for skill (M=9.87, SD=.42), Knowledge (M=7.68, SD=2.24) and satisfaction (M=43.07, SD=5.65) among traditional and Flipped class students. This study suggests that the teachers can be implement flipped classroom technique along with the traditional method of teaching.